# Sum over k of r by r+kt to the Power of k-1 over k Factorial by Power of z

Jump to navigation
Jump to search

## Theorem

Let $x$ be the continuous real function of $z$ which satisfies:

- $\ln x = z x^t$

where $x = 1$ when $z = 0$.

Then:

\(\displaystyle x^r\) | \(=\) | \(\displaystyle \sum_{k \mathop \ge 0} \dfrac {r \left({r + k t}\right)^{k - 1} } {k!} z^k\) | |||||||||||

\(\displaystyle \) | \(=\) | \(\displaystyle 1 + r z + \dfrac {r \left({r + 2 t}\right)} 2 z^2 + \cdots\) |

## Proof

## Sources

- 1997: Donald E. Knuth:
*The Art of Computer Programming: Volume 1: Fundamental Algorithms*(3rd ed.) ... (previous) ... (next): $\S 1.2.9$: Generating Functions: $(30)$